Simulation tool for learning of signals and systems theory - part B - Lim, Ginnie (Nanyang Technological University, 2022)
This report is concerned with the Final Year Project in creating a simulation tool to improve the learning of EE2010/IM2004 Signals and Systems taught at Nanyang Technological University. The module, Signals and Systems, is one of the core subjects in the field of engineering and it builds the foundation for students to proceed on to more advanced courses in Signal Processing, Communications and Control.